Understanding bilingual brain function and structure changes? U bet! A unified bilingual experience trajectory model - DeLuca, Vincent; Segaert, Katrien; Mazaheri, Ali; Krott, Andrea (Journal of neurolinguistics, 2020)
A growing body of research shows that the brain adapts functionally and structurally to specific bilingual experiences. These brain adaptations seem related to modulations in cognitive processes (specifically the executive functions). However, the trajectory of these adaptations is varied and seems at least partially dependent on different aspects of language exposure and use. Here we provide a review of the existing theoretical models covering bilingualism-induced neuroplasticity. Moreover, we propose a unifying framework (Unifying the Bilingual Experience Trajectories, UBET) to more comprehensively map the relationship between the various neurocognitive adaptations and different aspects of bilingual experience trajectories, focusing on intensity and diversity of language use, language switching, relative proficiency, and duration of bilingual experience. Crucially, we also outline predictions regarding both relationships between different bilingual experience factors and relationships between the measurable neurocognitive adaptations. Our framework offers a theoretical backdrop and clear testable predictions for future large-scale empirical studies on individual differences in bilingual trajectories and their effects on neurocognitive adaptations. •A framework linking together current models on bilingualism-induced neuroplasticity.•Distinct language experiences influence each other's neurocognitive effects.•Relationships between adaptations in brain structure, function, and cognitive processes.